Comparative Analysis between 18 F- PSMA-1007 and 18F-FDG PET-CT scans in Metastatic Prostate Carcinoma: A Case Report (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Prostate cancer is the second leading cause of cancer death in males and has a poor prognosis if present with metastasis. Proper management demands precise and reliable detection of the extent of disease, finally staging where molecular imaging plays the crucial role. The 18F PSMA-1007 PET-CT scan is more specific for the detection of prostate cancer. An 18F-FDG scan may be positive in prostate cancer when the tumor uses glucose metabolism or due to upregulation of glucose transporter-1. So, in case of aggressive or dedifferentiated prostate carcinoma, 18F-FDG PET-CT may provide precise localization of metastases. Case Report: A 78-year-old man with a history of hematuria consulted a physician, and after proper evaluation, he was diagnosed with a case of prostate cancer five years back. Transurethral resection of the prostate was done. During this interval period, the patient was not in follow-up, and no chemotherapy or radiotherapy was given. A follow-up ultrasound showed an enlarged prostate with heterogeneous parenchyma, and a biopsy from the prostate revealed adenocarcinoma (Gleason’s score 7-grade group 3) with a high serum PSA level of 52.06 ng/ml. This patient was referred to NINMAS for 18F-PSMA-1007 PET-CT scan to detect recurrence. The PSMA scan demonstrated local recurrence and metastases involving the lungs, liver, skeletal system, and lymph nodes. For academic purposes, a complementary 18F-FDG PET-CT scan was performed, which revealed more detailed information regarding the metastatic lesions, with higher FDG uptake (SUVmax) compared to PSMA uptake. Additionally, the FDG scan provided clearer delineation of hepatic metastases, which were less distinct on the PSMA scan due to the high physiological uptake of PSMA in the liver. Conclusion: These comparative imaging findings highlight the potential utility of 18F-FDG PET-CT in cases of atypical, aggressive, and dedifferentiated prostate cancer, providing complementary diagnostic insights beyond 18F-PSMA-1007 PET-CT.Bangladesh J. Nuclear Med. 29(1): 100-106, 2026